Friedrich Hayek and His Visits to Chile - Bruce Caldwell; Leonidas Montes (Duke University, Center for the History of Political Economy (CHOPE), 2014)
F. A. Hayek took two trips to Chile, the first in 1977, the second in 1981. The visits were controversial. On the first trip he met with Genera l Augusto Pinochet, who had led a coup that overthrew Salvador Allende in 1973. During his 1981 visit, Ha yek gave interviews that were published in the Chilean newspaper El Mercurio and in which he discussed authoritarian regimes and the problem of unlimited democracy. After each trip, he complained th at the western press had painted an unfair picture of the economic situation under the Pinochet regime. Drawing on archival material, interviews, and past research, we provide a full account of this controversial episode in Hayek's life.
Keywords: B1; B2; B25; B21; B3; B4; 330; F. A. Hayek; Chile; Chicago Boys; Augusto Pinochet; Salvador Allende; Milton Friedman; Centro de Estudios Publicos (CEP); El Mercurio